Design and Implementation of an Experimental Thermoelectric System From Wood Waste - Ngahane, Emilienne Laure; Maapou, Meguedong Kelly; Tchiofo, Lontsi Rodine (European Scientific Journal, ESJ, 2025)
This study was carried out at Dino & Fils SA, a wood processing unit in Soa-Cameroon. The aim was to recover energy from wood waste in order to contribute to greater energy flexibility in wood processing units. Specifically, the aim was to assess the quantity of wood waste available on the site and estimate its energy potential, to design and test a system for producing electrical energy from these waste and to estimate the contribution of this thermoelectric system to meeting the company’s energy needs and the associated costs. Wood waste were characterized by taking measurements at each station on the production line, supplemented by monthly production reports and scientific data. For the month of March 2024, the plant produced 3 284 m³ of wood waste, or 64% of the gross wood volume. This is equivalent to 2 766 tons for an electrical energy potential of 571 MWh; the company’s monthly electricity consumption is estimated at 121 MWh. The experimental thermoelectric system set up, using the TEC1-12715 Peltier module, produced electricity with a total power of 841 W and a Seebeck coefficient of 0.04 V°C⁻¹ by burning 5 kg of sawdust for 85 minutes. On a real scale and under optimum conditions, this system would be an effective and viable solution for covering not only all the energy needs of Dino & Fils SA but also those of surrounding households and offices at a competitive cost of 48 FCFA/kWh.